2023
DOI: 10.7759/cureus.45508
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Lung Cancer and Sarcoidosis: A Literature Review

Lotanna Umeano,
Hari Priya Pujari,
Syed Muhammad Zain Jamil Nasiri
et al.

Abstract: Lung cancer is responsible for a significant number of cancer-related deaths worldwide. While various factors can lead to lung cancer, such as tobacco smoking, this article focuses on the relationship between sarcoidosis, a multisystem granulomatous disorder, and lung neoplasm. To investigate this association, the authors conducted a literature search using relevant keywords. The analysis of these reports concluded that while Sarcoidosis and lung cancer together is rare, it is possible. The presenting symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The frequency of concurrent sarcoidosis and lung cancer is very low at <1%. 1 Sakula et al has reported three possible relationships between sarcoidosis and lung cancer: 3 reaction to lung cancer. (III) Sarcoidosis precedes the development of lung cancer, and the occurrence of lung cancer is entirely coincidental.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The frequency of concurrent sarcoidosis and lung cancer is very low at <1%. 1 Sakula et al has reported three possible relationships between sarcoidosis and lung cancer: 3 reaction to lung cancer. (III) Sarcoidosis precedes the development of lung cancer, and the occurrence of lung cancer is entirely coincidental.…”
Section: Discussionmentioning
confidence: 99%
“…Mediastinal lymphadenopathy looks like lung cancer metastasis on chest CT and PET‐CT. The frequency of concurrent sarcoidosis and lung cancer is very low at <1% 1 . Sakula et al has reported three possible relationships between sarcoidosis and lung cancer: 3 (I) Sarcoidosis precedes the development of lung cancer, connects and predisposes to the malignant change.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations